Study of acute kidney injury in children with nephrotic syndrome in a rural tertiary care hospital - Khichar, Babita; Jain, Rakhi; Yadav, Meetu (Asian Journal of Medical Sciences, 2024)
Background: Acute kidney injury (AKI) is a common comorbidity in critically ill children and is associated with an increased risk of morbidity and mortality in children with nephrotic syndrome. The etiology of AKI in nephrotic syndrome is complex and multifactorial. Aims and Objectives: To determine the proportion, risk factors, and outcomes of patients with AKI in children hospitalized with nephrotic syndrome. Materials and Methods: This cross-sectional study was done on children between 1 month and 14 years of age attending the pediatric department for 1 year from October 2020 to June 15, 2022. Detailed history, physical examination, and investigations were done in children with nephrotic syndrome as per pro forma. Information was collected on demographic variables, vital signs, anthropometry, diagnosis, comorbidities, therapies, presence of hypovolemia, sepsis or shock, use of diuretics or nephrotoxic medications, need for oxygen, mechanical ventilation, vasopressors or renal replacement therapy, length of hospital stay, and outcome at discharge. For those children having AKI, clinical outcomes were measured in terms of duration of hospital stay, recovery of S.creatinine, and urine output. Results: A total of 64 patients with nephrotic syndrome were enrolled in this study. Fifteen patients had AKI (23.4%) among children with nephrotic syndrome. The most common etiology being sepsis accounting for 4 out of 15 (26.7%) of total cases followed by acute respiratory distress syndrome (13.3%), nephrotoxic medications (13.3%), renal parenchymal disease (13.3%), Post-streptococcal glomerulonephritis (13.3% each) and Sickle cell disease with nephritis and acute fulminant hepatitis (6.7%). There was significantly more mortality among subjects with stage 2 (14.3%) and 3 (14.3%) kidney disease. Conclusion: AKI is common in our children with nephrotic syndrome and the main risk factors of AKI include sepsis, gross hematuria, urinary tract infections, peritonitis, and exposure to potentially nephrotoxic medications. There is a need to identify the patients with nephrotic syndrome at risk of AKI and apply strategies to prevent AKI in focused at-risk groups.